A Multi-Terminal Cathode Ray Tube System for Man-Computer-Interfacing - Reichertz, P. L.; Templeton, A. W.; DeLurgio, L. J. (Methods of Information in Medicine, 1968)
A FORTRAN compatible, Physician-Computer-Interfacing System (FCMTS) has been developed utilizing up to 24 cathode-ray tube terminals with one set of programs. The system is designed for IBM 360 computers (Model 40 and upwards) under OS and IBM 2260 terminals. It is written for local operation and interrupt control. Time consuming polling is not necessary.According to the intended application, a FORTRAN program set has to be supplied. It must consist of a sub-executive and application oriented task routines. The sub-executive controls the logic followed by the individual terminals. The task routines perform the different tasks of the application. FCMTS has been developed for ‘RADIATE’, a system for the synthesis, formatting and transmission of radiology reports. In its current version, up to 8 CRTs may be used at the same time. FCMTS may be utilized for diagnostic routines, for compilation of patient histories and data of physical examinations, and for any other dialogue between physician and computer.